Belajar Sejarah Melalui Pembelajaran Tari Topeng Cirebon di SDN 1 Ujungsemi - Nanda Septiyanti Hapsoh; Agus Budiman; Ria Sabaria (FBS Padang State University, 2023)
The creativity and skills of SBK in SD are enhanced through integrated dance, including character building and relationship with history. This study aims to find a way of learning art that is integrated with history lessons in elementary schools to increase early childhood creativity. This study took a sample of 36 grade 3 elementary school students with a focus on student experience and learning outcomes. Research methods: qualitative descriptive approach; data collection techniques: observation, interviews, and documentation. Findings: early childhood can understand subjects through an integrated approach, increasing creativity and character from an early age. As creators and implementers of blended learning, teachers play a role in planning, implementing, and evaluating through group discussions or blended learning simulations to improve the ability to implement blended learning. Interesting findings include learning history that is related to art and culture and the difficulties of the Cirebon clan Topeng Dance which is flexible for children aged 7-12 years to learn, with the hope that this phenomenal study will hone children's creativity and shape character from an early age.